2018
DOI: 10.1016/j.nicl.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal degree centrality in chronic users of codeine-containing cough syrups: A resting-state functional magnetic resonance imaging study

Abstract: Codeine-containing cough syrups (CCS) have become one of the most popular drugs of abuse in young population worldwide. However, the neurobiological mechanisms underlying CCS-dependence are yet ill-defined. Therefore, understanding the brain abnormalities in chronic users of CCS is crucial for developing effective interventions. The present study depicted the intrinsic dysconnectivity pattern of whole-brain functional networks at the voxel level in chronic users of CCS. In addition, the degree centrality (DC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…However, our findings show that functional connectivity changes simultaneously appeared in these regions. Based on the functional network integrity perspective, it could be postulated that the function of cognitive control-related regions was weakening [17]. Therefore, we hypothesized that deficits in cognitive control regulatory processes might occur in DEACMP patients during the resting state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our findings show that functional connectivity changes simultaneously appeared in these regions. Based on the functional network integrity perspective, it could be postulated that the function of cognitive control-related regions was weakening [17]. Therefore, we hypothesized that deficits in cognitive control regulatory processes might occur in DEACMP patients during the resting state.…”
Section: Discussionmentioning
confidence: 99%
“…DC represents the role and status of voxels in the brain network, and changes in DC indicate an anomaly between the functional synchronization of a particular node and other nodes. For example, increased DC values suggest an increased number of direct connections and reflect the increased centrality or importance of a specific voxel in the network [17]. DC was initially proposed to map the degree of intrinsic functional connectivity across the brain to reveal a stable property of cerebral network architecture at the voxel level [15].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies that examined adult smokers ( 37 ), and abstinent alcoholics ( 36 ), our study found significant cortical thinning in the middle temporal gyrus. The decreased degree of centrality in the middle temporal gyrus has been associated with language expression ( 76 ), attention, and cognitive deficits in addicts ( 77 , 78 ), suggesting a weakening of cognitive control in individuals with BQD.…”
Section: Discussionmentioning
confidence: 99%
“…Hua et al. (37) assessed the internal connectivity disorder pattern of the whole-brain function network in patients with chronic use of codeine-containing cough syrups (CCS) at the voxel level; notably, they found that the degrees of reduction in the left inferior parietal lobe and left middle temporal gyrus were associated with cognitive function in individuals dependent on CCS. Wang et al.…”
Section: Discussionmentioning
confidence: 99%